Politeness Strategies Between Asian Students and an Indonesian Teacher in English-as-a-Foreign Language Interactions - Kurniarahman, Iwan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2024)
The use of politeness by teachers and students in classroom interactions is one of the pragmatics subjects that have drawn a lot of attention. Although considered under-researched, politeness remains one of the most interesting topics, including in Indonesia. This study investigates the politeness strategies used by students from different countries during the learning process with a native Indonesian tutor. A mixed-method approach was used: qualitative method mainly described the politeness strategies, meanwhile a quantitative approach was used to determine the distribution of each type of strategy. The participant was one English teacher, an Indonesian native speaker, and nine students from three different countries, i.e., China, India, and Indonesia. Data collection was conducted using video recordings, followed by a structured process of analysis which involved transcription of the recorded interactions, coding key linguistic and behavioral elements, classifying them based on identified themes, and conducting a detailed analysis. The findings showed that only three politeness strategies were employed within the teacher-student interaction, i.e., Bald on Record, Positive Politeness, and Negative Politeness. Meanwhile, the Off-Record strategy was not used, possibly due to the need for direct and clear communication in the classroom setting, where avoiding ambiguity is crucial for effective instruction and language learning. The study suggests that teachers and students can use the study's findings as a reference to enhance their interactions.